The Influence of Organizational Justice on Interpersonal and Organizational Deviance: A Conceptual Paper - Dwi Wahyu Pril Ranto; Heru Kurnianto Tjahjono; Muafi Muafi; Wisnu Prajogo (International Journal of Marketing & Human Resource Research, 2022)
This research is a conceptual study that aims to investigate the influence of the organizational justice dimension on deviant behavior. The study’s main objective is to create an analysis of existing literature on the impact of organizational justice consisting of distributive justice, procedural justice, interpersonal justice, and informational justice on deviant behavior. The data search method used in this conceptual study is based on a literature review of journal articles obtained through an online database using keywords as a search tool. The study results revealed a negative influence of distributive, procedural, interpersonal, and informational justice on deviant behavior based on the existing literature. Such deviant behavior is directed at individuals and organizations.